Let $x_n$ and $y_n$ denote sequences such that: $$ \lim_{n\to\infty}(|x_n + y_n| - |x_n - y_n|) = +\infty $$ Prove: $$ \lim_{n\to\infty}(|x_n + y_n| - |x_n - y_n|) = +\infty \iff \lim_{n\to\infty}|x_n| =\lim_{n\to\infty}|y_n| =\lim_{n\to\infty}x_ny_n =+\infty $$

I've started with the first case ($\implies$): $$ \lim_{n\to\infty}(|x_n + y_n| - |x_n - y_n|) = +\infty \\ \stackrel{\text{def}}{\iff} \forall \epsilon > 0\ \exists N\in\Bbb N: \forall n>N \implies ||x_n + y_n| - |x_n - y_n|| \ge \epsilon $$

We want to show that $|x_n| \ge \epsilon$ and $|y_n|\ge \epsilon$. By triangular inequality: $$ |x_n + y_n| + |x_n - y_n| \ge ||x_n + y_n| - |x_n - y_n|| \ge \epsilon $$

At the same time: $$ |x_n + y_n| + |x_n - y_n| \ge |(x_n + y_n) + (x_n - y_n)| = 2|x_n| $$ Or: $$ |x_n + y_n| + |y_n - x_n| \ge |(x_n + y_n) + (y_n - x_n)| = 2|y_n| $$ Here is where the first questionable case comes in. It seems that: $$ |x_n + y_n| + |x_n - y_n| \ge 2|x_n| \ge ||x_n + y_n| - |x_n - y_n|| \ge \epsilon\\ \text{and}\\ |x_n + y_n| + |y_n - x_n| \ge 2|y_n| \ge ||x_n + y_n| - |x_n - y_n|| \ge \epsilon \tag1 $$

But I'm not sure how to justify that. I've checked various cases like $x<0 \land y<0$ and 3 others, for all it seems to hold. So based on this: $$ \forall \epsilon >0 \ \exists N\in\Bbb N: \forall n> N \implies 2|x_n| \ge \epsilon \\ \forall \epsilon >0 \ \exists N\in\Bbb N: \forall n> N \implies 2|y_n| \ge \epsilon $$

Which shows: $$ \lim_{n\to\infty}|x_n| = \lim_{n\to\infty}|y_n| = +\infty $$

In this part I'm interested in how to justify $(1)$ and where from it follows that: $$ \lim_{n\to\infty}x_ny_n = +\infty $$

Second case $(\impliedby)$. This case I've no idea where to start from. We basically given three things: $$ \forall \epsilon > 0\ \exists N\in\Bbb N: \forall n>N \implies |x_n| \ge \epsilon\\ \forall \epsilon > 0\ \exists N\in\Bbb N: \forall n>N \implies |y_n| \ge \epsilon \\ \forall \epsilon > 0\ \exists N\in\Bbb N: \forall n>N \implies |x_ny_n| \ge \epsilon $$

The problem is I don't see where to go from this.

Could you please verify the overall reasoning and help with ($\impliedby$) and question from ($\implies$), I still often have troubles with constructing those proofs since i'm a self-learner and have no one to refer to. Thank you!


$(\Longrightarrow)$ Note that by triangle inequality, we have $$ 2|x_n|=|(x_n+y_n)+(x_n-y_n)|\ge|x_n+y_n|-|x_n-y_n| $$ and $$ 2|y_n|=|(x_n+y_n)-(x_n-y_n)|\ge|x_n+y_n|-|x_n-y_n|. $$ By taking $n\to\infty$, we get $$ \lim_{n\to\infty}|x_n|=\lim_{n\to\infty}|y_n|=\infty. $$ Also note that $ |x_n+y_n|\ge |x_n-y_n| $ holds eventually. Hence, by squaring both sides, we have $x_ny_n\ge 0$. It follows that $\lim_{n\to\infty}x_n y_n=\lim_{n\to\infty}|x_n| |y_n|=\infty.$

$(\Longleftarrow)$ To show the converse, note that $\lim_{n\to\infty}x_n y_n=\infty$ implies that $$ |x_n+y_n|-|x_n-y_n|\ge 0 $$ eventually. And since it is a positive sequence, we have $$ \lim_{n\to\infty}|x_n+y_n|-|x_n-y_n|=\infty \Longleftrightarrow \lim_{n\to\infty}\left[|x_n+y_n|-|x_n-y_n|\right]^2=\infty. $$ Now, we have $$ \left[|x_n+y_n|-|x_n-y_n|\right]^2= 2(|x_n|^2+|y_n|^2) -2|x_n^2-y_n^2|=:L. $$ Observe that if $x_n^2\ge y_n^2$, then it holds $L=4|y_n|^2$ and otherwise, $L=4|x_n|^2$. This gives $L=4 \min\{|x_n|^2,|y_n|^2\}$ and $$ \lim_{n\to\infty}\left[|x_n+y_n|-|x_n-y_n|\right]^2= 4\lim_{n\to\infty}\min\{|x_n|^2,|y_n|^2\}=\infty $$ by the assumption that $\lim_{n\to\infty}|x_n|=\lim_{n\to\infty}|y_n|=\infty$. This proves the converse claim.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.